2009
DOI: 10.3177/jnsv.55.361
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Oral Polyamine Intake Increases Blood Polyamine Concentrations

Abstract: Summary Although the intracellular de novo synthesis of the polyamines decreases with age, there is no similar trend in blood polyamine levels, but rather there is wide individual variability. We hypothesized that dietary polyamines attenuate a decrease in blood polyamine levels with age and augment the previously observed individual variability. The effect of a polyamine rich diet, in both mice and humans, on blood polyamine concentrations was examined in this study. Jc1:ICR male mice were fed test diets cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
113
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(125 citation statements)
references
References 17 publications
9
113
1
2
Order By: Relevance
“…In Japan, fermented soybean is called "natto". It is reported that the long-term intake of natto increases levels of Spm in the blood of human volunteers (Soda et al, 2009). Our previous studies have shown that polyamines persist throughout the natto production processes (Kobayashi et al, 2016(Kobayashi et al, , 2017 and additional Spd was produced by B. subtilis (natto).…”
mentioning
confidence: 99%
“…In Japan, fermented soybean is called "natto". It is reported that the long-term intake of natto increases levels of Spm in the blood of human volunteers (Soda et al, 2009). Our previous studies have shown that polyamines persist throughout the natto production processes (Kobayashi et al, 2016(Kobayashi et al, , 2017 and additional Spd was produced by B. subtilis (natto).…”
mentioning
confidence: 99%
“…A long-term intake of polyamine-rich foods is shown to gradually increase blood polyamine levels in humans and animals (11). By taking into consideration the average daily intake (35 mL per day) of drinking water containing 3 mM SPM, rats are supposed to be daily given 100 μmol of SPM for 28 consecutive days under our experimental protocols.…”
mentioning
confidence: 99%
“…In our studies, we have shown that polyamines contained abundantly in soybeans inhibit the progression of age-associated pathological changes and prolong mouse lifespan. Importantly, we found that the favorable effects of food polyamines on murine health and longevity were not due to differences in food intake or changes in body weight, but rather considered due to the polyamine-mediated suppression of inflammatory mediators (Soda et al, 2005(Soda et al, , 2009a(Soda et al, , 2009b. In this chapter, I discuss the possible contributions to human health of polyamines present in dietary soybeans.…”
Section: Introductionmentioning
confidence: 98%